2022
DOI: 10.1128/mbio.01454-22
|View full text |Cite
|
Sign up to set email alerts
|

A Multitrait Locus Regulates Sarbecovirus Pathogenesis

Abstract: Host genetic variation is an important determinant that predicts disease outcomes following infection. In the setting of highly pathogenic coronavirus infections genetic determinants underlying host susceptibility and mortality remain unclear.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 60 publications
(93 reference statements)
1
18
0
Order By: Relevance
“…Schäfer showed that knocking out two of the six ortholog genes in this region, CCR9 and CXCR6 , prevented recovery from SARS‐CoV‐2 infection, increased inflammatory response and mortality, and was associated with prolonged lung dysfunction. This study validates the collaborative cross as a platform to identify and validate novel susceptibility genes that regulate emerging virus pathogenesis across species 86 …”
Section: Innate Immunity and Evasionsupporting
confidence: 64%
See 3 more Smart Citations
“…Schäfer showed that knocking out two of the six ortholog genes in this region, CCR9 and CXCR6 , prevented recovery from SARS‐CoV‐2 infection, increased inflammatory response and mortality, and was associated with prolonged lung dysfunction. This study validates the collaborative cross as a platform to identify and validate novel susceptibility genes that regulate emerging virus pathogenesis across species 86 …”
Section: Innate Immunity and Evasionsupporting
confidence: 64%
“…Schäfer used the genetically diverse collaborative cross mice to identify strains that demonstrate a range of phenotypes to SARS‐CoV infection in terms of weight loss, viral titers, and mortality. These phenotypes were associated with a quantitative trait locus that clustered in a region on chromosome 9 86 . Several of these genes display synteny with genes identified in a human GWAS study that correlate with COVID‐19 disease severity 87,88 .…”
Section: Innate Immunity and Evasionmentioning
confidence: 97%
See 2 more Smart Citations
“…; https://doi.org/10.1101/2023.03. 18.533278 doi: bioRxiv preprint CoV-2 19 , and influenza A virus 20 , and also to map the genetic determinants responsible for complex phenotypic traits 13 .…”
Section: Introductionmentioning
confidence: 99%